Holocene temperature, humidity and seasonality in northern New Zealand linked to Southern Hemisphere summer insolation. (1st December 2018) - van den Bos, Valerie; Rees, Andrew; Newnham, Rewi; Vandergoes, Marcus; Wilmshurst, Janet; Augustinus, Paul
Abstract: The Holocene thermal maximum (HTM) is a spatio-temporally variable period of generally warmer conditions during the early and middle Holocene that is often used as an analogue for future climate change. Global scale climate reconstructions and models tend to smooth out the variations and complexity of the HTM and inconsistencies between reconstructions from different locations and proxies are often attributed to bias arising from different locations or proxies. We use these differences as a source of information about seasonality and precipitation during the Holocene in a multi-proxy investigation of the sediments of Lake Pupuke, northern New Zealand. The sediments, spanning the last 16 kyr, were analysed for pollen, from which mean annual air temperatures (MAAT) and effective precipitation were estimated, and chironomids, from which summer air temperature (SmT) was estimated. We found no evidence for an HTM in the MAAT reconstruction, questioning the validity of treating the early-to-mid Holocene as an analogue for future climate change in northern New Zealand. SmT increases between 10 and 3 cal kyr BP, correlating strongly with integrated local summer insolation. Early-Holocene low seasonality (from 12 to 9.3 cal kyr BP) was likely driven by low local summer insolation intensity. An early-to-mid-Holocene wet period (9.6–7.5 cal kyr BP) corresponds to relatively high southern westerly wind (SWW) strength. Mid-to-late-Holocene summers following the wet period were hot and dry, especially 4.0–2.4 cal kyr BP, allowing the tall conifer, kauri ( Agathis australis ) to expand throughout northern New Zealand. Low effective precipitation at this time is consistent with increased evapotranspiration due to higher SmT, although reduced precipitation due to southward displaced SWW or increased El Niño frequency may also have contributed. Highlights: Temperature and precipitation records (16–0 kyr) from Lake Pupuke are reported. No Holocene Thermal Maximum was found during the early or middle Holocene. Climate proxies correlate strongly with local to regional insolation parameters.